Growth and Yield of Rice (Oryza sativa L.) on various planting pattern and addition of organic fertilizers - Sri Hariningsih Pratiwi (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2016)
The aim of this study is to examine the effect of planting pattern and organic fertilizers to growth and yield ofrice (Oryza sativa L.). The research was carried out at January - May 2015 in Toyaning Village, Rejoso Regency, Pasuruan, 2 m above the sea level with alluvial soil type and an average temperature of 22oC-31oC. Research applied with Random Group Design with six treatments: conventional Planting move (Tapin) without organic manure, Jajar legowo (JA) without organic manure, SRI without organic manure (SA), conventional Planting move with organic manure (TO), Jajar legowo with organic manure (JO), SRI with organic manure (SO). The results showed the pattern jajar legowo give best expression plant heigh, the dry weight of the plant top at age 14 day after plant (HST), grain weights/compartments, and net weighted/acres. Conventional planting move gives better response on the dry weight of the plant top at 50 HST, and dry weights bottom plant at 14 HST. The SRI planting pattern give best response number of saplings and the number of saplings of productive/clump, grain weight/clump, and weight of 1000 grain. The treatment of planting pattern with the addition of organic manure gives higher yields rather than without organic manure. Yield of Jajar Legowo is 10.2 tons/ha, highest than other 10.1 2 ton/ ha for Tapin and 68.05 ton/ha for SRI